PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI SPLDV DI SMP NEGERI 2 TONDANO - Togatorop, Elisabet; Wenas, Jhon R.; Tumalun, Nicky K. (SOSCIED, 2024)
This study aims to determine the effect of using problem-based learning model on students' mathematics learning outcomes in cognitive aspects. The method used in this research is quantitative research method with Quasi-Experimental Design research design. The population in the study were VIII grade students of SMP Negeri 2 Tondano in the 2024/2025 academic year consisting of 4 classes. The samples taken were VIII A class with 29 students as the experimental class and VIII B class with 24 students as the control class. The sampling technique was carried out using simple random sampling technique. In this study, the instrument used was a post-test test instrument in the form of an essay. The test statistic used to test the hypothesis is the t test. The results of the study using the t test obtained = 4.79 and = 1.67 with a real level of 5%. Because then reject and accept which means the hypothesis is accepted. Thus, it can be concluded that there is an effect of students' mathematics learning outcomes on the material of the system of linear equations of two variables through the use of problem-based learning models.